x = first child
x +2 = 2nd child
x+ 4 = 3rd child
It doesn't matter if the ages are odd or even - there is two years between each child in age.
The sum would be
x + x + 2 + x + 4 or 3x + 6.
Lets try it with a sample age. Let's say the youngest is 5 middle is 7 and oldest is 9
The sum of their ages is 21 (5 + 7 + 9)
Using our answer of 3x + 6 where x is the age of the youngest child, we get
3(5) +6 which is also 21.
This could also be solved by having x represent the middle age child
x-2 is the youngest (2 years less than the middle)
x = the middle
x+2 is the oldest (2 years older than the middle)
The sum of these would be x-2 + x + x +2 or simply 3x (the 2's cancel out)
Since the middle child is 7 3x would mean 3 (7)=21
You could also set this up using x for the oldest child
x= oldest
x-2= middle
x-4= youngest (The sum of this is 3x - 6)
3 (9) -6 is also 21.